Pathways to sustainable landscape management: peer recognition as an indicator of effective 'soft' actions. Issue 1 (2nd January 2016) - Swaffield, Simon; Winchester, Henry
Abstract : New Zealand is a food producer and exporter that combines neoliberal policy with performance-based environmental management, using 'soft' governance and actions where possible. Voluntary environmental farm awards are analysed to identify the landscape management activities recognised as best practice by peers at a farm level. Results highlight the importance of whole farm system management. However, the efficacy of reliance upon voluntary mechanisms is coming under increasingly critical scrutiny, as environmental conditions in intensive agricultural landscapes continue to decline. The research question this poses is whether whole farm plans can be practically and formally connected in three concurrent ways – to supply chain management, and to statutory planning frameworks and environmental regulations and to local landscape co-management – while still maintaining flexibility of action for the farmer.